Kekerasan Terhadap Anak Marginal Di Perkotaan - Soetji Andari (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2018)
Children who come from the marginalized child workers, street children, because poverty, helplessness or marginal family strife. There is nothing either parent due to death or family function can not cause a child to become a victim of violence. The exploitation of children are exacerbated by the presence of physical or emotional violence against children. The purpose of this research is to uncover the facts, circumstances, the phenomenon of violence. A descriptive qualitative research methods to interpret data and talk to suit the situation that occurs in, attitude and views that occurs in society. Doing research on the marginal population, totalling 60 children, gathering data through interviews and interview guide. Marginalized urban children who became victims of violence will experience physical trauma or psikisnya. They have experienced violence in the past can potentially do violence.